2016
DOI: 10.3402/ljm.v11.31086
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control status among type 2 diabetic patients and the role of their diabetes coping behaviours: a clinic-based study in Tripoli, Libya

Abstract: BackgroundAchieving good glycaemic control is important in diabetes management. However, poor glycaemic control is widely reported. This article assessed the prevalence of uncontrolled and poor glycaemic control among Libyans with type 2 diabetes and examined the relative contribution of diabetes coping behaviours to their glycaemic control status.MethodsA cross-sectional study was undertaken in 2013 in a large diabetes centre in Tripoli. The study included 523 respondents. Diabetes coping behaviours were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
37
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 33 publications
15
37
4
1
Order By: Relevance
“…Most of respondents in this study were married. This is consistent with another study in Coastal Kenya where 77% of the respondents were married and another in Tripoli, Libya where 76.9% were married [29,30]. However the results are lower than a study in India on T2DM where 98.7% of the respondents were married while another study in Ethiopia on T2DM patients showed 65.1% as married [31,32].…”
Section: Discussionsupporting
confidence: 85%
“…Most of respondents in this study were married. This is consistent with another study in Coastal Kenya where 77% of the respondents were married and another in Tripoli, Libya where 76.9% were married [29,30]. However the results are lower than a study in India on T2DM where 98.7% of the respondents were married while another study in Ethiopia on T2DM patients showed 65.1% as married [31,32].…”
Section: Discussionsupporting
confidence: 85%
“…Ten included studies evaluated foot care among diabetes patients from which two studies investigated foot care only (Shown in Table ). Six studies (Al‐Amer et al, ; Ashur et al, ; Assah et al, ; Bhandari & Kim, ; Mogre, Abanga, et al, ; Mosha & Rashidi, ) reported foot care adherence according to the mean number of days diabetes patients adhered to foot care recommendations; mean days ranged from 2.2–4.3 days in a week. Huang et al () reported a mean foot care practice score of 77.47% among Chinese persons with diabetes (higher scores indicate better self‐perceived overall foot care).…”
Section: Resultsmentioning
confidence: 99%
“…The study instruments have been previously used by other studies [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Mosleh Et Almentioning
confidence: 99%
“…The other part covered patient clinical characteristics data including medical history, type II diabetes duration, body mass index, smoking status, and any medications. The medical history question was presented to the participant as a list of illnesses with a dichotomous (yes/no) response [6,7]. All participants were asked to state their current antidiabetic treatment to investigate the antidiabetic therapy type as well as insulin treatment during the past 1 year.…”
Section: Sociodemographic and Health Questionnairementioning
confidence: 99%
See 1 more Smart Citation